Variation in Prescription Drug Coverage for Triptans: Analysis of Insurance Formularies. Issue 8 (9th July 2017) - Minen, Mia T.; Lindberg, Kate; Langford, Aisha; Loder, Elizabeth
Abstract : Objectives: To analyze triptan coverage by insurers to examine (1) possible disparities in coverage for different formulations (oral, intranasal, etc) and (2) quantity limits and stepped care requirements to obtain triptans. Background: Triptans are FDA approved migraine abortive medications. Patients frequently state that they have difficulty accessing triptans prescribed to them. Methods: We searched the 2015 drug formularies of commercial and government health insurers providing coverage in NY State. We created a spreadsheet with all of the commercially available triptans and included information about covered formulations, tier numbers and quantity limits for each drug. We then calculated the number of listed plans that cover or do not cover each triptan or triptan formulation, the total number of medications not covered by an insurance provided across all of its plans, as well as the percentage of plans offered by individual companies and across all companies that covered each drug. We also calculated the number and proportion of plans that imposed quantity limits or step therapy for each drug. Results: Of the 100 formularies searched, generic sumatriptan (all formulations), naratriptan, and zolmitriptan tablets were covered by all plans, and rizatriptan tablets and ODTs were covered by 98% of plans. Brand triptans were less likely to be covered: 4/36 Medicaid plans covered brand triptans. Commercial insurers were more likely to cover brand triptans. All plans imposed quantity limits on 1+ triptan formulations, with >80% imposing quantity limits on 14/19 formulations studied. Almost all plans used tiers for cost allocation for different medications. Generic triptans were almost always in Tier 1. Brand triptans were most commonly in Tier 3. Approximately 40% of brand triptans required step therapy, compared with 11% of generic triptans. Conclusions: There are substantial variations in coverage and quantity limits and a high degree of complexity in triptan coverage for both government and commercial plans.